Digital Divide in Educational Transformation in East Nusa Tenggara: A Focused Literature Review of Distance Learning and Academic Ability Test Readiness - Yohanes Kopong Geroda; Rugaiyah Rugaiyah; Muh. Takdir (Journal of Educational Sciences, 2026)
Educational digital transformation in Indonesia has expanded through distance learning, digital platforms, and technology-based assessment, yet unequal access remains a concern in archipelagic and disadvantaged, frontier, and outermost regions such as East Nusa Tenggara. This study aimed to synthesize evidence on the educational digital divide and examine its implications for distance learning and readiness for the digitally administered Academic Ability Test. A qualitative focused literature review analyzed 32 substantive sources selected through database and institutional-repository searches using predefined inclusion and exclusion criteria. Structured extraction, qualitative content analysis, and thematic coding generated six overlapping themes: digital infrastructure, device access, cost and connectivity, digital literacy, school readiness, and assessment fairness. The synthesis identified recurring patterns linking unstable connectivity, electricity constraints, inadequate or shared devices, affordability barriers, uneven digital competence, and limited institutional support with restricted participation in digital learning and testing. School readiness and digital literacy were most prominent in the reviewed corpus, whereas direct evidence on assessment fairness was more limited. These findings are literature-based patterns rather than causal field estimates. Equitable digital transformation therefore requires context-sensitive infrastructure, affordable access, strengthened digital competence, school-level readiness mapping, and adaptive assessment arrangements.